Effective Learning Strategies in Increasing Students Environmental Awareness at Vocational School Tri Bhakti At Taqwa - Putra, Bayu; Setiawan, Dedi; Ehwanudin, Ehwanudin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The aim of this research is to evaluate Islamic Religious Education (PAI) learning methods that are effective in increasing students' awareness of the environment in class X of Tri Bhakti At Taqwa Vocational School. It is very important to instill environmental awareness from an early age in this increasingly complex era of globalization, especially through education based on religious values. This research was conducted using a qualitative approach using observation, interviews and documentation as data collection methods. The research results show that PAI learning strategies that combine religious values with environmental issues can increase students' awareness of the importance of preserving the environment. Students not only gain religious knowledge but are also actively involved in environmental preservation through discussions, simulations and project-based learning activities that focus on the environment. Therefore, effective PAI learning strategies are very important to develop students' characteristics that care about the environment.